1992
DOI: 10.1038/bjc.1992.350
|View full text |Cite
|
Sign up to set email alerts
|

Haemostatic changes and thromboembolic risk during tamoxifen therapy in normal women

Abstract: SummaryTamoxifen has been implicated as a risk factor for venous thrombosis in advanced breast cancer although the evidence for increased arterial or venous thrombosis with tamoxifen in early breast cancer is less clear. The effect of tamoxifen on haemostasis, and thereby possible thromboembolic risk, was investigated in normal women enrolled in a placebo controlled trial of tamoxifen as a chemopreventative agent for breast cancer. There was an initial reduction in fibrinogen levels in all women on tamoxifen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 28 publications
(27 reference statements)
0
16
0
1
Order By: Relevance
“…Tamoxifen induces a hypercoagulable state by decreasing certain anticoagulatory factors such as antithrombin III and proteins C and S. 11,12 Kelley et al 7 also hypothesized that the antagonism of tamoxifen at vascular ERs may lead to inhibition of vasodilation and inflammation secondary proliferation of endothelial smooth muscle. The contribution of tamoxifen in arterial thrombosis is less clear.…”
Section: Discussionmentioning
confidence: 98%
“…Tamoxifen induces a hypercoagulable state by decreasing certain anticoagulatory factors such as antithrombin III and proteins C and S. 11,12 Kelley et al 7 also hypothesized that the antagonism of tamoxifen at vascular ERs may lead to inhibition of vasodilation and inflammation secondary proliferation of endothelial smooth muscle. The contribution of tamoxifen in arterial thrombosis is less clear.…”
Section: Discussionmentioning
confidence: 98%
“…At 70 months, no significant difference in the incidence of deep vein thrombosis or pulmonary embolism was observed between groups. A significant fall in total plasma cholesterol occurred within 3 months and was sustained over 5 yr of treatment (142, 213,214). The decrease affected low-density lipoproteins with no change in apolipoproteins A and B or high-density lipoprotein cholesterol.…”
Section: A Royal Marsden Pilot Studymentioning
confidence: 95%
“…If it exerts purely agonist properties on the coagulation system, than an increased risk of VTE would be expected biologically, as an association between oral estrogens and VTE is well-documented [32,33]. However, it is not clear that tamoxifen's influence on the coagulation system is purely agonistic, as evidence for a possible antagonist effect comes from studies that showed no change in markers of activated coagulation or fibrinolysis, including prothrombin F 1.2 , fibrin degradation products (FDP), or thrombin-antithrombin complex (TAT) [26,27,31,34].…”
Section: Mechanisms Of Increased Thrombosismentioning
confidence: 98%
“…While the association between tamoxifen and increased risk of VTE is well-documented, the exact mechanism is Versus placebo unclear, with most studies, but not all, reporting significant decreases in levels of ATIII, protein C, and protein S [23][24][25][26][27][28][29][30][31]. As tamoxifen has mixed partial estrogen agonist/ antagonist properties, it is not known if tamoxifen exerts a purely estrogen agonist effect on the coagulation system.…”
Section: Mechanisms Of Increased Thrombosismentioning
confidence: 99%